Determination of the frequency of carbapenemase producing Klebsiella pneumoniae isolates in Dhaka city, Bangladesh - Hayder, Nawshad; Hasan, Zahidul; Afrin, Sadia; Noor, Rashed (Stamford Journal of Microbiology, 2013)
Resistance of Klebsiella pneumoniae against carbapenem, imparted by the presence of carbapenemase, is an emerging global health problem with high morbidity and mortality. Thus, the present study attempted to detect the frequency of carbapenemase producing K. pneumoniae in Dhaka city of Bangladesh and thereby determine the health risk associated with their presence. A total of 647 K. pneumoniae isolates were detected from 2800 patients with urinary tract infection, bacterimia, wound infections and respiratory diseases. Thirty one carbapenem resistant isolates were found to harbor K. pneumoniae carbapenemase (KPC) through modified Hodge test. The KPC positive isolates were then subjected to the study of antibiogram and showed resistance against all the ß-lactam antibiotics along with carbapenems, while they were sensitive against colistin. Additionally, 287 isolates were found to be extended-spectrum ?-lactamases (ESBLs) positive apart from the KPC positive ones. DOI: http://dx.doi.org/10.3329/sjm.v2i1.15210 Stamford Journal of Microbiology, Vol.2(1) 2012: 28-30